کتاب الشفا میں معجزات رسول ﷺ کے متعلق روایات کا تحقیقی وتجزیاتی مطالعہ: Research and Analytical Study of the Narrations related to the Miracles of the Prophet (P.B.U.H) in the book Al-Shifa - Dr. Muhammad RAfiq, (MEI, 2023)
A miracle is a supernatural thing that is given to every prophet by God as a proof of the authenticity of his prophecy. The Prophet (peace and blessings of Allaah be upon him) was blessed with innumerable miracles of various kinds by Allaah. Ibn Taymiyyah has mentioned more than a thousand of them. From the time of compilation of Islamic sciences, biographers have made the miracles of the Prophet (P.B.U.H) the especial subject of their writings. One of them is Qazi Ayyaz, who dedicated a whole chapter of his book Al-Shifaa to miracles. He mentioned about 321 miracles. In this article, after describing the definition, conditions and types of miracles using the descriptive and inductive method, mentioning 22 selected miracles from them, according to Qazi Ayaz's claim that all these are proven by authentic narrations, after their authentication, research and analysis, it has been found that this claim is disputable; because some of them are weak narrations and some are even fabricated, which should not be narrated without explanation of their fals.